Karakteristik Habitat Peneluran Penyu di Calon Kawasan Konservasi Perairan Taman Pesisir Lunyuk dan Tatar Sepang - Lalu Ilham Syaputra; Dwi Mardhia; Dedi Syafikri (Indonesian, 2020)
The sandy beach where turtles lay their eggs is a natural incubator and has a suitable environment for the development of turtle embryos. Microclimate suitable for incubation of turtle eggs arises from interactions between physical characters, beach compilers, the local environment and eggs in the nest. One of the locations where sea turtles land and lay eggs in West Nusa Tenggara Province is on the beach of Lunyuk, Sumbawa Regency. Receiving sea turtles is a protected endangered species, it is necessary to carry out conservation activities to protect and save sea turtles. To support efforts to support, it is necessary to support locations where turtles lay their eggs. Like discussing research on landing sites and turtle nesting sites. The purpose of this study was to analyze the level of suitability of habitat characteristics for turtle nesting in the Lunyuk beach area. The research method uses the survey method. Survey activities include field observations and collecting primary data. Data analysis was performed using the weighting and scoring method. Based on observations it can be seen, the slope of the beach which is the location of spawning is 6.54 - 11.1%, substrate temperature 27 ° C - 32 ° C, humidity substrate 25% - 40%. While the percentage of vegetation is 40% - 57.1%. From the station visit, stations 1 and 2 are quite suitable, while stations 3, 4 and 5 are categorized according to the location of turtle nesting.